The Risk Involved in Implementation of Innovations in the Real Estate Market - Marcin Sitek (Institute of Economic Research (IER), 2017)
Research background: In this paper a short overview of the types of innovations and their innovative forms of investing in the real estate market, such as reverse mortgage, flipping, building for rent, system condo and crowdfunding was presented. Purpose of the article: The aim of the paper is to present risk factors in innovative activities in the real estate market and evaluation of their activity in this market. The study proposed the hypothesis that a specific level of development in the real estate market corresponds to a certain level of investment risk reflected by the rate of return. Methodology/methods: The questionnaire survey in the local real estate market participants (investors, employees in enterprises that provide services for the real estate market, external appraisers, real estate brokers and counsellors) was conducted for the purposes of evaluation of risk factors in the investment innovative activities. Findings: Analysis of the results of questionnaire survey supported the following thesis: (1) as an effect of a strong inflow of capital and disturbed balance between demand and supply, return rates represent the reaction to the previous market behaviours, (2)decline in the rates of return points to the increase in the investment risk in the real estate market. It was found that the particularly high contribution to the risk level is from market risk, which is little transparent in Poland and is characterized by high variability of the conditions of operation.
Keywords: E32; E44; F63; O12; O31; 330; risk; investment risk; innovations; risk management